LOCAL DEMOCRACY TRENDS IN GEORGIA - Todorovski, Ilija; Ilik, Goran (European Scientific Journal, ESJ, 2014)
Georgia is a country that gravitates towards Europe with strong tendencies to join the European Union. Since the early 1990-ties it has been undergoing the process of political reforms towards political pluralism and overall democratization, slowed by the civil war and war waged for its territorial integrity. The last period 2004-2014 is the one that promoted and speeded up the process of democratization especially at local level. These developmental trends were the subject of our analysis as concerning three very important areas: devolution of competencies or transfer of competencies from central to local authorities, fiscal decentralization and relations between central and local authorities. In this respect the research findings proved limited progress in respect to devolution of competencies and fiscal decentralization that provided some own revenues for local authorities and opportunities to freely dispose with some of the state grants as well as introducing criteria and supervisory procedures in exerting state administrative and financial control over local organs, but still the system is burdened by the centralistic tendencies, reaching the general conclusion that the Georgian local government in the last period (2004-2014) has made considerable developmental progress in comparison to the former periods but the system can be still characterized by fundamental restrictions in its functioning.